Methods of main bronchus stump closure and incidence of bronchopleural fistula after pneumonectomies for lung cancer (a retrospective single center review) - Cicėnas, Saulius; Jackevičius, Algirdas; Aškinis, Renatas; Krasauskas, Arnoldas; Šileika, Nerijus; Samalavičius, Narimantas Evaldas; Naujokaitis, Pranas (Acta medica Lituanica, 2014)
Background. Bronchopleural fistulas (BPFs) development after pneumonectomy remains a serious complication and is associated with high mortality rate. We evaluated incidence and risk factors, that influenced BPF rate after pneumonectomies for lung cancer patients treated at the Department of Thoracic Surgery and Oncology of the Institute of Oncology, Vilnius University, and compared different bronchial stump suturing techniques. Methods. It is a retrospective study. We reviewed 580 lung cancer patients who underwent pneumonectomies from January 1990 to January 2009. The average patient’s age was 60.1 ± 7.9 years (range from 34 to 76). Patients according to postoperative staging: stage IIA – 30 patients, IIB – 80, IIIA – 320, IIIB – 96, IV – 54. The most common tumor histology was planocellular carcinoma – 301, adenocarcinoma – 108, small-cell carcinoma – 76. Results. There were 327 (56.4%) right and 253 (43.6%) left pneumonectomies. Mediastinal lymph node dissection (LND) was performed to 387 (66.7%) and lymph node sampling (LNS) to 193  (33.3%) patients. The bronchial stump was covered in 285 (49.1%) patients. Bronchopleural fistula after pneumonectomy developed in 48 (8.3%) patients (bronchial dehiscence was confirmed by bronchoscopy), and 7 patients with BPF died (14.5%). BPF after right pneumonectomy occurred in 30 cases (9.5%) and after left pneumonectomy in 18 cases (7.1%), the difference was not statistically significant (p > 0.05). BPF after LND occurred in 38 cases (9.82%) and after LNS in 10 cases (5.18%), the diff erence was statistically significant (p